Matching-adjusted indirect comparison of efficacy outcomes for ciltacabtagene autoleucel in CARTITUDE-1 versus idecabtagene vicleucel in KarMMa for the treatment of patients with relapsed or refractory multiple myeloma. (3rd October 2021) - Martin, Tom; Usmani, Saad Z.; Schecter, Jordan M.; Vogel, Martin; Jackson, Carolyn C.; Deraedt, William; Tian, Hong; Yeh, Tzu-min; Banerjee, Arnob; Pacaud, Lida; Garrett, Ashraf; Haltner, Anja; et al.
Abstract: Objective: This study estimated the comparative efficacy of ciltacabtagene autoleucel (cilta-cel) versus the approved idecabtagene vicleucel (ide-cel) dose range of 300–460 × 10 6 CAR-positive T-cells for the treatment of patients with relapsed or refractory multiple myeloma (RRMM) who were previously treated with a proteasome inhibitor, an immunomodulatory drug, and an anti-CD38 monoclonal antibody (i.e. triple-class exposed) using matching-adjusted indirect treatment comparisons (MAICs). Methods: MAICs were performed with individual patient data for cilta-cel (CARTITUDE-1; NCT03548207) and published summary-level data for ide-cel (KarMMa; NCT03361748). Treated patients from CARTITUDE-1 who satisfied the eligibility criteria for KarMMa were included in the analyses. The MAIC adjusted for unbalanced baseline covariates of prognostic significance identified in the literature and by clinical expertise. Comparative efficacy was estimated for overall response rate (ORR), complete response or better (≥CR) rate, duration of response (DoR), progression-free survival (PFS), and overall survival (OS). Results: Cilta-cel was associated with statistically significantly improved ORR (odds ratio [OR]: 94.93 [95% confidence interval [CI]: 21.86, 412.25; p  < .0001]; relative risk [RR]: 1.34), ≥CR rate (OR: 5.49 [95% CI: 2.47, 12.21; p  < .0001]; RR: 2.21), DoR (hazard ratio [HR]: 0.50 [95% CI: 0.29, 0.87; p =  .0137]), and PFS (HR: 0.37 [95% CI: 0.22, 0.62; p  = .0002]) when compared with ide-cel. For OS, the results were in favor of cilta-cel and clinically meaningful but with a CI overlapping one (HR: 0.55 [95% CI: 0.29, 1.05; p  = .0702]). Conclusions: These analyses demonstrate improved efficacy with cilta-cel versus ide-cel for all outcomes, highlighting its therapeutic potential in patients with triple-class exposed RRMM.